Project study of Esca's (Garden restaurant) - Cortes, Menchie; Bugacia, Kathleen Rose; Lacar, Khristianne Karla; Quino, Cyrose; Santoyo, Evelyn; Sales, May Jane
This study was conducted on the 9th day of July to 14th day of September 2007, aimed to know the operations management of Esca's Garden restaurant that is located in Aurora Subdivision, Iloilo City. The main purpose of the study is for the researchers to apply the principles and theoris that are learned inside the classroom in actual business setting and also to instigate innovations for the improvement of the company's operation. Data were gathere through observation, and interviews. The researchers interviewed Mr. Rafael Cordova, the owner; Mrs Louise Cordova, the mother of the owner and the one-in-charge with the financial matters and supplies in the company; and Ms. jennifer Griego, the marketing and operation head. The data were analyzed and result showed that Esca's Garden Restaurant by Afriques has a smooth operation. They em-loy effective and effecient processes in their operations that greatly increase their profit.